Treatment of gastric varices with cyanoacrylate complicated by systemic embolization - de Sousa, Cristina Peixoto (2024)
Acute gastric variceal bleeding is a life-threatening condition that could be effectively treated with endoscopic cyanoacrylate injection diluted with lipiodol. The mixture acts as a tissue adhesive that polymerizes when in contact with blood in a gastric varix. This work reports a patient that presented to the emergency department with upper gastrointestinal bleeding due to acute variceal bleeding, who developed systemic embolization following cyanoacrylate injection therapy. This complication culminated in cerebral, splenic and renal infarctions with a fatal outcome. Systemic embolization is a very rare, but the most severe complication associated with endoscopic cyanoacrylate injection and should be considered in patients undergoing this treatment.